The princes who had no fortune - Jones , Ursula (Orchard books, London, 2014)
The Princess Who Had No Fortune by Ursula Jones, illustrated by Sarah Gibb. Published by Orchard Books on October 1, 2015, this 32-page paperback is aimed at younger readers aged 5 to 8. It presents a contemporary fairy tale about a princess who lacks traditional riches and a prince in shining armor, yet finds herself intrigued by a mysterious young man who arrives at her castle offering assistance. The story is a witty and romantic tale of love and mistaken identity, serving as a follow-up to the bestselling The Princess Who Had No Kingdom.